Metal ion selectivity and molecular modeling - Comba, Peter (Coordination chemistry reviews, 1999)
The evaluation of ligand molecules that are able to coordinate selectively specific metal ions is a difficult task. Possible applications range from metal refinement and detoxification of industrial waste to medical applications and the desire to understand biological processes. Molecular mechanics modeling was used to predict highly preorganized ligand systems and the molecular mechanics design, followed by the synthesis of size selective macrocyclic donors was used extensively in this area. So far, only few truly successful studies have emerged, and some of these are reviewed. The limitations of the models used are highlighted, the reasons for expected pitfalls are discussed and possible models to solve some of the remaining problems are analyzed.
Gesehen am 14.03.2018